Synthesis multicomponent based on o‐tolyl‐isocyanide; cholinesterase inhibitors and computational studies (2022)
Isocyanide-based multicomponent reactions turn out to be interesting synthetic strategies, with highly valued advantages such as atomic economy, selectivity, among others. Furthermore, Isocyanide-based multicomponent reactions have been shown to generate a wide range of products with significant biological activity. Recently, it has been described that the compounds of the Isocyanide-based multicomponent reactions product could be inhibitors of cholinesterase enzymes, acetylcholinesterase, and butyrylcholinesterase. cholinesterase enzymes have aroused great interest as pharmacological targets in the treatment of Alzheimer's disease, which is a disease that affects millions of people in the world, and its effects become disabling for those who suffer from it since it mainly has consequences on memory and cognitive ability. In this work, using Isocyanide-based multicomponent reactions, we report a series of five new compounds, their characterization, and their potential inhibitory biological activity on acetylcholinesterase and butyrylcholinesterase by spectrophotometric analysis. Our studies revealed that the compounds have moderate inhibitory activities against acetylcholinesterase and butyrylcholinesterase. Interestingly, compounds 7a and 7e showed a higher affinity for butyrylcholinesterase. Particularly compound 7a proved to be the compound with the best activity of this series with an IC50 of 25.91 µM for butyrylcholinesterase, more than 62.22 times selective for butyrylcholinesterase than for acetylcholinesterase. The study of molecular docking and molecular dynamics revealed that the hydrophobic character of these compounds favors the interaction with BChE. The favored interactions for compounds 7a and 7e are with the hydrophobic residues Trp82, Trp231, Val288, Phe329, Thr120. In addition, the molecular electrostatic potential and pharmacokinetic predictions also showed that compounds 7a and 7e have free energy values close to galantamine in the complex with butyrylcholinesterase, among others. These analyzes will allow us in the future to establish some structural modifications that would enable, on this basis, to obtain compounds with better activity against cholinesterase enzymes